AJIC Issue 27, 2021 - Full Issue - print-on-demand version - (:unkn) unknown (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2021)
Articles on problematic internet use (PIU), Indigenous knowledge in vocational education, machine learning, scaling of innovation, institutional isomorphism, human–computer interaction for development (HCI4D), and scholarly publishing.